ATF4/TXNIP/REDD1/mTOR signaling mediates the antitumor activities of liver X receptor in pancreatic cancers. Issue 1 (30th June 2022) - Chen, Zhikang; Lai, Xiaobo; Ding, Hui; Zhang, Aijun; Sun, Yufei; Ling, Jianhua; Chiao, Paul J.; Chen, Zihua; Xia, Xuefeng
Abstract: Background: Limited by difficulties in early detection and availabilities of effective treatments, pancreatic cancer is a highly malignant disease with poor prognosis. Nuclear receptors are a family of ligand‐dependent transcription factors that are highly druggable therapeutic targets playing critical roles in human physiological and pathological development, including cancer. In this study, we explored the therapeutic potential as well as the molecular mechanisms of liver X receptor (LXR) agonist GW3965 in pancreatic cancer. Methods: Soft‐agar colony formation assay, xenograft tumors, Oligonucleotide microarray, Reverse transcription real‐time polymerase chain reaction, Western immunoblotting and Immunohistochemistry were used in this study. Results: We demonstrated pleotropic in vitro activities of GW3965 in pancreatic cell lines MIA PaCa‐2 and BXPC3 including reduction of cell viability, inhibition of cell proliferation, stimulation of cell death, and suppression of colony formation, which translated to significant inhibition of xenograft tumor growth in vitro . By mapping the gene expression profiles, we identified the up‐regulations of 188 and the down‐regulations of 92 genes common to both cell lines following GW3965 treatment. Genes responsive to GW3965 represent a variety of biological pathways vital for multiple cellular functions. Specifically, we identified that the activating transcription factor 4/thioredoxin‐interacting protein/regulated in development and DNA damage responses 1/mechanistic target of rapamycin (ATF4/TXNIP/REDD1/mTOR) signaling critically controls GW3965‐mediated regulation of cell proliferation/death. The significance of the ATF4/TXNIP/REDD1/mTOR pathway was further supported by associated expressions in xenograft tumors as well as human pancreatic cancer samples. Conclusions: This study provides the pre‐clinical evidence that LXR agonist is a promising therapy for pancreatic cancer. Abstract : In this study, Chen's team demonstrated pleiotropic anticancer activities of liver X receptor (LXR) agonist GW3965 in pancreatic cancer, both in vitro and in vivo. They identified the critical role and clinical significance of ATF4/TXNIP/REDD1/mTOR signaling in GW3965‐induced anticancer phenotypes. These novel findings reveal that the LXR agonist is a promising therapy for pancreatic cancer.